Epidural anesthesia in patients with chronic coronary syndrome undergoing non-cardiac surgery - Miranti I. Kumesan; Diana Ch. Lalenoh; Wahyuddin Suleman (Indonesian Journal of Health Science, 2026)
Patients with cardiovascular disease, particularly Chronic Coronary Syndrome (CCS), face high perioperative risks, including myocardial ischemia, arrhythmias, and hemodynamic instability. Appropriate anesthetic management aims to maintain the balance between oxygen supply and demand as well as hemodynamic stability, including through the use of regional anesthesia techniques as a safer alternative. We report the case of a 71-year-old male patient, ASA III, with CCS accompanied by valvular heart disease in the form of mild aortic regurgitation and moderate pulmonary regurgitation, who underwent Percutaneous Nephrolithotomy (PCNL). Anesthesia management utilized a lumbar epidural technique with catheter placement at the L1–L2 level, 6 cm intradural, and administration of 12 ml of 0.75% ropivacaine. The intended block coverage included the T10–L2 viscerotome and the T8–S2 dermatome. Hemodynamic and pain assessments were performed periodically during the intraoperative period and in the post-anesthesia care unit (PACU). The block depth reached the target within 20 minutes, allowing the surgery to begin immediately. During the 2-hour and 25-minute procedure, the patient’s hemodynamics remained stable without complaints of chest pain or shortness of breath, and no additional anesthetic agents were required. In the PACU, the patient’s sensory and motor functions returned to normal with a NRS pain score of 1. The epidural regional anesthesia technique in a patient with CCS undergoing non-cardiac surgery was shown to facilitate hemodynamic stability intra- and postoperative pain control, thereby potentially significantly minimizing the risk of perioperative ischemia.